PERSPECTIVES OF PRE-SERVE EFL TEACHERS TO CHOOSE TEACHING AS A FUTURE CAREER - Rita, Erinda Nalu; Wulandari, Sri; Putri, Kristanti Yuntoro; Haryanti, Dhena Usthiana (Jurnal Pendidikan Bahasa Inggris Proficiency, 2024)
Globalization has had a massive impact on people’s mindset nowadays when on deciding their career, especially on being a teacher. In this case, working in the educational sector is considered a non-profitable occupation, especially for being a teacher. Due to those issues, this research aimed to analyze the career pre-serve EFL teachers and the motivations affecting their decision to be a teacher at the Islamic University of Kadiri in 2023/2024. This study used descriptive qualitative as the research design, where the data was collected by conducting in-depth interviews. Nine university students in the 8th semester of English Education were chosen as participants. The interview results have shown that motivation is the best way to prepare students to deal with the challenge of current teaching conditions. Having a strong motivation could lead them to a successful teaching career. All in all, considering a future career as a teacher is a great choice, since the students have figured out the current situation of the teachers following by some obstacles teachers have faced. Due to this condition, this job surprisingly brings great opportunities await in the future. Key words: future career, motivation, pre-serve teacher